Analyzing the maximum output of residential PV in low‐voltage distribution networks considering voltage‐dependent loads. Issue 8 (6th April 2018) - Sugihara, Hideharu; Funaki, Tsuyoshi
Abstract : Voltage rise is a significant problem in low‐voltage distribution networks where individual load characteristics might arise easily. In this paper, we develop a method for evaluating the maximum output of a photovoltaic (PV) system by considering voltage‐dependent loads in residential low‐voltage distribution networks. The influence of voltage‐dependent load on the maximum PV output is examined. Furthermore, the impact of electric vehicle charging load on the maximum PV output is analyzed by taking into account its voltage‐dependent characteristics. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.